The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1590/s0104-66322011000300013
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nickel and magnesium on zinc electrowinning using sulfate solutions

Abstract: -Zinc electrowinning is performed with the application of a current through insoluble electrodes (Pb-Ag), causing the electrolysis of zinc sulfate, with or without impurities, and zinc deposition on the cathode of aluminum. The impurities can reduce the current efficiency and increase the energy consumption in zinc electrolysis. In this work, the effect of nickel and magnesium on zinc electrodeposition was studied using the electrochemical techniques of galvanostatic deposition and cyclic voltammetry. Addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 12 publications
(16 reference statements)
1
14
0
Order By: Relevance
“…In contrast to the onset potential of silver electrodeposition at the 1st scan cycle, the reduction of silver ions starts at a more positive potential from the 2nd scan cycle onwards, which is at ∼−280 mV. As platinum working electrode (which is different from the deposited metal) is employed, the initiation of nucleation normally consumes more energy to produce the first nucleus [20]. Besides that, the presence of nondissolved silver film on the electrode may also facilitate the nucleation and growth processes during the 2nd scan cycle.…”
Section: Cyclic Voltammetry Of Ag/ag + At Rotating Disk Platinummentioning
confidence: 98%
“…In contrast to the onset potential of silver electrodeposition at the 1st scan cycle, the reduction of silver ions starts at a more positive potential from the 2nd scan cycle onwards, which is at ∼−280 mV. As platinum working electrode (which is different from the deposited metal) is employed, the initiation of nucleation normally consumes more energy to produce the first nucleus [20]. Besides that, the presence of nondissolved silver film on the electrode may also facilitate the nucleation and growth processes during the 2nd scan cycle.…”
Section: Cyclic Voltammetry Of Ag/ag + At Rotating Disk Platinummentioning
confidence: 98%
“…High purity (99.999%) silver single crystals with specific orientations of the (100), (110) and (111) were purchased from Goodfellow Cambridge Ltd, UK. These one-sided polished single crystals have diameter of 10 mm and thicknesses of 2 mm for the (100) and (111) samples and 1 mm for the (110) sample. The orientation tolerance of these single crystals was ± 3º.…”
Section: Methodsmentioning
confidence: 99%
“…2D (Ra) and 3D (Sdr) roughness parameters were used to characterize the surface texture of single crystal silver. It is found that surface roughness plays a more critical role in determining the reflectance while the crystal (100), (110) and (111) orientations have negligible effect on the silver reflectance. Moreover, correlations in predicting the silver reflectance by employing either 2D or 3D roughness parameters as the input variables have also been proposed.…”
Section: /7/2017mentioning
confidence: 99%
See 2 more Smart Citations